2015
DOI: 10.1097/ruq.0000000000000082
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Findings of Typical and Atypical Scrotal Trauma

Abstract: This review article illustrates sonographic findings in the setting of accidental and nonaccidental scrotal trauma. Although sonographic findings may be irrespective of the type of trauma, the goals of sonographic evaluation are similar in both atypical and typical mechanisms of scrotal injury. Familiarity with findings such as disruption of testicular integrity or vascularity facilitates prompt diagnosis and plays a critical role in clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In cases of segmental infarction due to epididymo-orchitis, it has been suggested that venous compromise can result in a rounded lesion (30). The median age of patients with segmental infarction is 37 years, which over- hematomas are avascular, a helpful distinguishing feature from seminoma (34). If there is concern about an incidental testicular tumor discovered at testicular US performed for trauma, follow-up imaging to ensure resolution should be performed.…”
Section: Benign Lesions Segmental Infarctionmentioning
confidence: 99%
“…In cases of segmental infarction due to epididymo-orchitis, it has been suggested that venous compromise can result in a rounded lesion (30). The median age of patients with segmental infarction is 37 years, which over- hematomas are avascular, a helpful distinguishing feature from seminoma (34). If there is concern about an incidental testicular tumor discovered at testicular US performed for trauma, follow-up imaging to ensure resolution should be performed.…”
Section: Benign Lesions Segmental Infarctionmentioning
confidence: 99%
“…Acute trauma uncommonly affects the scrotum, and scrotal trauma when it does occur is usually due to blunt force trauma (4). Aside from risks of acute trauma, bicycle riding may be associated with chronic genital trauma, including scrotal numbness due to pudendal compression, associated with regional genital(penile, perineal) numbness, as well as sometimes with erectile dysfunction.…”
Section: Lesions and Neoplasms Of The Scrotum Traumamentioning
confidence: 99%